Changes in Relative Work of the Lower Extremity and Distal Foot Joints After Total Ankle Replacement: An Exploratory Study - Paul-Andre Deleu; Alexandre Naaim; Bernhard Devos Bevernage; Laurence Cheze; Raphael Dumas; Ivan Birch; Jean-Luc Besse; Thibaut Leemrijse (IEEE, 2023)
Ankle osteoarthritis does not only led to lower ankle power generation, but also results in compensatory gait mechanics at the hip and Chopart joints. Much of previous work explored the relative work distribution after total ankle replacement (TAR) either across the lower extremity joints where the foot was modelled as a single rigid unit or across the intrinsic foot joints without considering the more proximal lower limb joints. Therefore, this study aims, for the first time, to combine 3D kinetic lower limb and foot models together to assess changes in the relative joint work distribution across the foot and lower limb joints during level walking before and after patients undergo TAR. We included both patients and healthy control subjects. All patients underwent a three-dimensional gait analysis before and after surgery. Kinetic lower limb and multi-segment foot models were used to quantify all inter-segmental joint works and their relative contributions to the total lower limb work. Patients demonstrated a significant increase in the relative ankle positive joint work contribution and a significant decrease in the relative Chopart positive joint work contribution after TAR. Furthermore, there exists a large effect toward decreases in the relative contribution of the hip negative joint work after TAR. In conclusion, this study seems to corroborate the theoretical rationale that TAR reduces the compensatory strategy in the Chopart and hip joints in patients suffering from end-stage ankle osteoarthritis.